The role of ultrasonography for detecting tip location of percutaneous central venous catheters in neonates-a single-center, prospective cohort study - Hsin-Chun Huang; Li-Ting Su; Yu-Chen Liu; Hsin-Yu Chang; Mei-C; Mei-Yung Chung; Feng-Shun Chen; Chih-Cheng Chen; I-Lun Chen (Elsevier, 2021)
Background: Percutaneous central venous catheters (PCVCs) are used commonly and widely in the neonatal intensive care unit (NICU). Malposition of PCVCs may cause life-threatening complications and prolong hospitalization. In Taiwan, conventional chest-abdomen radiography (CXR) has been used widely and routinely for assessing tip location of PCVCs. Compared to ultrasonography (US), CXR cannot provide real-time assessment, and patients are exposed to radiation. Therefore, this study aimed to analyze the role of US in detecting PCVC tip location in the lower extremities. Methods: Neonates who received PCVC insertion in the lower extremities in NICU from March 2019 to April 2020 were enrolled in this prospective cohort study. PCVC tip location was confirmed finally by conventional CXR after US examination and patients were included in the sono group; those not assessed by US formed the non-sono group. In addition, PCVCs inserted in 2018 for which tip location was evaluated only by CXR, were reviewed retrospectively and these cases were included in the non-sono group. Withdrawal rates between the two groups were analyzed using Chi-square test. Results: The sono group included 166 neonates with PCVCs and 141 were in the non-sono group. Median gestational age at date of PCVC insertion was 33.21 and 32.71 weeks in sono and non-sono groups, respectively (p = 0.37). Withdrawal rates were 10.84% and 65.95% (p < 0.001) and duration for catheter location confirmation were 2-4.75 min and 75-247.25 min (p < 0.001), respectively. Conclusion: US provides more reliable images than conventional radiography alone for identifying PCVC tip locations in the lower extremities. It can effectively reduce catheter insertion duration, and was associated with fewer manipulations.